Justification of the methodology for installing a deformation recorder in a main pipeline section through analysis of its stress-strain state - Slabyi, Orest; Shlapak, Lubomyr; Grydzhuk, Jaroslav; Deineha, Ruslan; Popovych, Vasyl (Technology audit and production reserves, 2025)
Object of the research is a deformation recorder designed for monitoring the stress-strain state of main pipelines. This study investigates the hypothesis regarding the feasibility of installing a deformation recorder on a pipeline section that has been preloaded with the maximum allowable operating pressure, in order to ensure the recorder’s reliable performance under various pipeline operating conditions. Structurally, the examined deformation recorder consists of two clamps, with four longitudinal strain multipliers mounted at diametrically opposite locations between them. By comparing their relative strain values, it is possible to determine the spatial curvature of the pipeline axis. A 3D model of a pipeline section with a diameter of 270 mm and wall thickness of 5 mm was developed, incorporating a deformation recorder with a measurement base of 300 mm. Based on this model, a multi-step finite element model was created to calculate the stress-strain state and the contact interaction of a 4.6-meter-long pipeline section. One end of the pipeline was modeled as axially compliant, and the stress recorder was installed on it. Series of numerical experiments were conducted to analyze the stress-strain behavior of the assembly under varying preload forces of the clamp bolts. The results confirmed the initial hypothesis and allowed the determination of an acceptable preload range. Specifically, the preload force must be no less than 15 kN to ensure secure attachment of the clamps on a non-operational pipeline, and must not exceed 30 kN to comply with the pipeline’s strength requirements. Based on the analysis, recommendations were made regarding the development of a redesigned clamp lock. Additionally, the study proposes that changing the material of the deformation recorder may reduce the required bolt preload force.